2003
DOI: 10.1002/cncr.11174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an internet support group for women with primary breast cancer

Abstract: A versatile, ultralight, N‐doped, 3D graphene framework (GF) is prepared. In their Communication on L. Qu and co‐workers show that this GF has an ultra‐low density ((2.1±0.3) mg cm−3; a GF block can balance on a dandelion) and its adsorption capacity for oils is much higher than that of the best carbonaceous sorbents. The 3D open‐pore structure and N doping make GF promising as an electrode material for supercapacitors and as a metal‐free catalyst for the oxygen reduction reaction in fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
314
1
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(337 citation statements)
references
References 57 publications
9
314
1
13
Order By: Relevance
“…Peer support from long-term survivors of prostate cancer was found to be effective in reducing depressive symptoms in men who had recently undergone a radical prostatectomy when assessed at 4 weeks (P ¼ 0.02), but not at 8 weeks, follow-up (Weber et al, 2004). A web-based social support group was also found to be effective in reducing depressive symptoms in women with primary breast cancer when assessed at the end of the 12 weeks intervention (ES ¼ 0.54) (Winzelberg et al, 2003).…”
Section: Psychotherapeutic Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Peer support from long-term survivors of prostate cancer was found to be effective in reducing depressive symptoms in men who had recently undergone a radical prostatectomy when assessed at 4 weeks (P ¼ 0.02), but not at 8 weeks, follow-up (Weber et al, 2004). A web-based social support group was also found to be effective in reducing depressive symptoms in women with primary breast cancer when assessed at the end of the 12 weeks intervention (ES ¼ 0.54) (Winzelberg et al, 2003).…”
Section: Psychotherapeutic Studiesmentioning
confidence: 97%
“…Studies were conducted in Europe (n ¼ 5) (Burton et al, 1995;Marchioro et al, 1996;McArdle et al, 1996;Moynihan et al, 1998;Kuijer et al, 2004), the United States of America (n ¼ 8) (Evans and Connis, 1995;Sandgren et al, 2000;Antoni et al, 2001;Classen et al, 2001;Rawl et al, 2002;Winzelberg et al, 2003;Given et al, 2004;Weber et al, 2004) Canada (n ¼ 1) (Goodwin et al, 2001), Australia (n ¼ 3) (Edelman et al, 1999;McLachlan et al, 2001;Petersen and Quinlivan, 2002) and Japan (n ¼ 1) (Fukui et al, 2000). The mean sample size in the intervention and control group was 61 patients (range 15 -296) and 52 patients (range 15 -154), respectively.…”
Section: Psychotherapeutic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…90 In one study, 72 women were randomly assigned to either a 12-week web-based social support group for women with breast cancer (with a semi-structured, asynchronous newsgroup format moderated by a health care professional) or waitlist control. 91 Effect sizes were moderate and participants perceived a variety of benefits and high satisfaction with the group. A similar study reported on the clinical outcomes Rehabilitation, Disability and Ageing for 32 women with breast cancer who participated in professionally facilitated and "closed" OSGs for 1.5 hours weekly over 16 weeks.…”
Section: Acceptability Of Videoconferencingmentioning
confidence: 99%
“…The most impressive study to date, a randomized controlled trial with recipients of a breast cancer mailing list, suggests that a Web-based support group can be useful in reducing depression and cancer-related trauma as well as perceived stress. 72 In summary, the overall "net benefits" of virtual communities, in particular in the health context and even more specifically for persons with cancer, are unclear, and there is a lack of high-quality controlled trials addressing these questions. 59 It is likely that most persons with cancer benefit from virtual communities, whereas a minority may prefer local face-toface support and might not feel comfortable using computers to build social relationships.…”
Section: What Is the Effect Of Virtual Communities On Well-being And mentioning
confidence: 99%